A Stimulated Emission Diagnostic Technique for Electron Temperature of the High Power Radio Wave Modified Ionosphere - H. Y. Fu; M. L. Jiang; J. Vierinen; I. Häggström; M. T. Rietveld; E. Varberg; H. Sato; J. Wu; W. A. Scales; Y. Q. Jin (Geophysical Research Letters)
Abstract We report observations of stimulated electromagnetic emission (SEE) induced by high power high frequency (HF) radio waves near the third electron gyroharmonic (3fce) at European Incoherent Scatter Radar (EISCAT). It is discovered that stimulated Brillouin scattering (SBS) spectrum behaves similarly as spectral ion lines of the incoherent scatter radar (ISR) for HF pumping frequency above 3fce. The SBS spectral width shows correlation with electron to ion temperature ratio Te/Ti. A new inversion method is proposed by incorporating the SBS spectral width within an artificial neural network approach to achieve electron temperature inversion for ionospheric turbulent plasmas. This work provides a potential new technique to diagnose parameters in the modified ionosphere when the ISR is not available.